2000
DOI: 10.1177/019262330002800111
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-Jade: Novel Fluorochromes for Detecting Toxicant-Induced Neuronal Degeneration

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(151 citation statements)
references
References 33 publications
(59 reference statements)
11
138
0
1
Order By: Relevance
“…Finally, the neurotoxic effects of MDMA may not be limited to serotonergic neurons. Schmued (2003) found that high doses of MDMA led to cellular damage in the rat forebrain (where no serotonergic somata are present) as indicated by staining with Fluoro-Jade B, a marker for neurodegeneration that has been validated with several known neurotoxins (Schmued and Hopkins, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the neurotoxic effects of MDMA may not be limited to serotonergic neurons. Schmued (2003) found that high doses of MDMA led to cellular damage in the rat forebrain (where no serotonergic somata are present) as indicated by staining with Fluoro-Jade B, a marker for neurodegeneration that has been validated with several known neurotoxins (Schmued and Hopkins, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One basic prerequisite is perfused tissue, otherwise erythrocytes will also be highlighted and interfere with signals from degenerating cells. Fluoro-Jade B is an anionic dye reportedly specific for soma and neurites of degenerating neurons under various pathologic conditions, including ischemia (Schmued and Hopkins, 2000), although there are reports that describe labeling of microglia and astrocytes under certain conditions (Damjanac et al, 2007;Saganova et al, 2006). Owing to the high sensitivity of Fluoro-Jade B, detection of degenerating neurons as early as 1.5 hours after a 90-minute MCAO in mice is possible (Liu et al, 2009).…”
Section: Light Microscopy and Macroscopymentioning
confidence: 99%
“…FJB staining was performed according to the method described by Schmued and Hopkins [28]. Additional sections were used to assess double-label fluorescence immunohistochemistry with FJB using primary antibody to glial fibrillary acidic protein (GFAP) or Neuronal Nuclei (NeuN) in a concentration of 1:1000 (GFAP) or 1:400 (NeuN), and a secondary antibody tagged with a fluorophore (Alexa Fluor 555, Invitrogen, Eugene, OR) in a concentration of 1:500.…”
Section: Fjb Histochemistrymentioning
confidence: 99%
“…Additional sections were used to assess double-label fluorescence immunohistochemistry with FJB using primary antibody to glial fibrillary acidic protein (GFAP) or Neuronal Nuclei (NeuN) in a concentration of 1:1000 (GFAP) or 1:400 (NeuN), and a secondary antibody tagged with a fluorophore (Alexa Fluor 555, Invitrogen, Eugene, OR) in a concentration of 1:500. FJB and 4'6'-diamidino-2-phenyllindole (DAPI) double staining was performed using previously described methods [28,35,41].…”
Section: Fjb Histochemistrymentioning
confidence: 99%
See 1 more Smart Citation